XRCC7 rs#7003908 Polymorphism and Helicobacter pylori Infection-Related Gastric Antrum Adenocarcinoma - Chao Wang; Xiao-Ying Huang; Jin-Guang Yao; Bing-Chen Huang; Cen-Han Huang; Pinhu Liao; Xi-Dai Long (International Journal of Genomics)
The X-ray repair cross-complementing group 7 (XRCC7) plays a key role in DNA repair that protects against genetic instability and carcinogenesis. To determine whether XRCC7 rs#7003908 polymorphism (XRCC7P) is associated with Helicobacter pylori (H. pylori) infection-related gastric antrum adenocarcinoma (GAA) risk, we conducted a hospital-based case-control study, including 642 patients with pathologically confirmed GAA and 927 individually matched controls without any evidence of tumours or precancerous lesions, among Guangxi population. Increased risks of GAA were observed for individuals with cagA positive (odds ratio (OR) 6.38; 95% confidence interval (CI) 5.03–8.09). We also found that these individuals with the genotypes of XRCC7 rs#7003908 G alleles (XRCC7-TG or -GG) featured increasing risk of GAA (ORs 2.80 and 5.13, resp.), compared with the homozygote of XRCC7 rs#7003908 T alleles (XRCC7-TT). GAA risk, moreover, did appear to differ more significantly among individuals featuring cagA-positive status, whose adjusted ORs (95% CIs) were 15.74 (10.89–22.77) for XRCC7-TG and 38.49 (22.82–64.93) for XRCC7-GG, respectively. Additionally, this polymorphism multiplicatively interacted with XRCC3 codon 241 polymorphism with respect to HCC risk (ORinteraction=1.49). These results suggest that XRCC7P may be associated with the risk of Guangxiese GAA related to cagA.